TikTokers da ciência: uma análise da produção de conteúdo de divulgação científica - Jesus, Thaís Santos de (Universidade Federal de São Carlos, 2025)
Scientific dissemination provides non-specialist citizens with the opportunity to effectively participate in public debates, decision-making, and conscious choices in their daily lives, through inputs provided by the circulation and cognition of contextualized scientific information. In this area, social media stands out by moving from being a source of entertainment to becoming a source of information. TikTok, the object of analysis of this research, stands out as a potential channel for scientific dissemination and has been used by influencers and researchers who are able to quickly approach scientific information for young users who seek content on this platform, often to the detriment of traditional sources of information. This descriptiveexploratory research with quantitative and qualitative approaches has the general objective of investigating Brazilian digital influencers (researchers) who use TikTok for scientific dissemination and analyzing the content (topics) they address. To structure the research, a bibliographic survey was carried out to compose the theoretical framework and select science TikTokers (researchers) – the latter action was carried out in search engines and on the platform itself (TikTok), based on a previous protocol. An alternative model of Bardin's content analysis was applied to collect and analyze the data. The interpretation of the 407 published contents shows that the scientific dissemination model applied on the platform can affect the development of information practices and media competence of followers who consume scientific information. It was clear that not all TikTokers invest in sharing information with references/sources, reducing the possibility of followers developing an interest in the topic/subject outside the platform. When analyzing the content of the TikTokers investigated, it was observed that the narrative structure is maintained to share more contextualized scientific information, especially that categorized as curiosities. Digital influencers, by acting as mediators of scientific knowledge, can play an important role in the democratization of information and in strengthening scientific literacy in digital environments.
Science TikTokers: an analysis of science communication content production
Keywords: Informação científica.; TikTok.; Mídias sociais.; Divulgação científica.; Práticas informacionais.; Competência em Informação; Scientific information.; TikTok.; Social media.; Scientific dissemination.; Information practices.; Information competence.; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO::TEORIA DA INFORMACAO; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO::BIBLIOTECONOMIA; 9. Indústria, Inovação e Infraestrutura